Robert Morrison and the Protestant plan for China - Daily, Christopher A. (Hong Kong : Hong Kong University Press, 2013)
Robert Morrison, sent alone to his East Asian post by the London Missionary Society in 1807, was the first Protestant missionary to operate in China. During some 27 years in China, Macau and Malacca, he worked as a translator, founded an academy for converts and missionaries, translated the New Testament into Chinese and compiled the first Chinese-English dictionary. In this process, he was building the foundation of Chinese Protestant Christianity. Today, Chinese Protestant Christianity becomes one of the largest Christian churches in the world and the fastest growing religion in China. This.
Acknowledgements -- Introduction -- The birth of British evangelicalism and the disappointment of the earliest LMS missions -- The new approach to missions : Gosport Academy and David Bogue's strategy -- Looking towards China : Morrison's work in London and the voyage to China -- Communicating the Gospel to China : Robert Morrison uses Bogue's programme to propagate to the Chinese -- The Ultra Ganges Mission Station, a printing centre, and the final educational step of the template -- Notes -- Bibliography -- Index.
Includes bibliographical references (pages 239-253) and index.
Print version record.
Keywords: Morrison, Robert, -- 1782-1834.; Protestantism -- China -- History; Missionaries -- Great Britain -- Biography; Missionaries -- China -- Biography; Morrison, Robert, -- 1782-1834.; HISTORY -- Asia -- China; RELIGION -- Christian Ministry -- Missions; Morrison, Robert, -- 1782-1834.; Missionaries; Protestantism; China; Great Britain; Morrison, Robert -- 1782-1834; Missionar; China; Electronic books; Biography; History